2022
DOI: 10.1021/acs.est.1c08671
|View full text |Cite
|
Sign up to set email alerts
|

Even Incorporation of Nitrogen into Fe0 Nanoparticles as Crystalline Fe4N for Efficient and Selective Trichloroethylene Degradation

Abstract: Surface modification of microscale Fe powder with nitrogen has emerged recently to improve the reactivity of Fe0 for dechlorination. However, it is unclear how an even incorporation of a crystalline iron nitride phase into Fe0 nanoparticles affects their physicochemical properties and performance, or if Fe0 nanoparticles with a varied nitridation degree will act differently. Here, we synthesized nitridated Fe0 nanoparticles with an even distribution of N via a sol–gel and pyrolysis method. Nitridation expanded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…3(d)). 45,46 It is noteworthy that the band center of graphitic/pyrrolic N in Fe-SNC-0.2 was ∼0.2 eV blue-shifted as compared to Fe-NC, meaning that the N atoms in Fe-SNC- Environmental Science: Nano Paper 0.2 are in a more reductive state, which is probably due to the close incorporation of the S atom. Moreover, it was found that Fe-SNC-0.2 had a more abundant graphitic/pyrrolic N content (12.0 at%) (Table S4 †), indicating that the type of iron salt in the precursor was crucial to the N-doped level.…”
Section: Characterization Of the Fe-sncmentioning
confidence: 99%
“…3(d)). 45,46 It is noteworthy that the band center of graphitic/pyrrolic N in Fe-SNC-0.2 was ∼0.2 eV blue-shifted as compared to Fe-NC, meaning that the N atoms in Fe-SNC- Environmental Science: Nano Paper 0.2 are in a more reductive state, which is probably due to the close incorporation of the S atom. Moreover, it was found that Fe-SNC-0.2 had a more abundant graphitic/pyrrolic N content (12.0 at%) (Table S4 †), indicating that the type of iron salt in the precursor was crucial to the N-doped level.…”
Section: Characterization Of the Fe-sncmentioning
confidence: 99%
“…18 Theoretical calculations show lattice N and P in a Fe (110) plane can provide hydrophobicity as that of lattice S. 59 Even incorporation of N into nFe 0 could improve the materials' hydrophobicity and electron transfer, providing efficient and selective trichloroethylene (TCE) degradation, despite the N being present as crystalline Fe 4 N rather than being incorporated into the Fe crystal. 56 It could be concluded that impregnating a Fe crystal lattice with nonmetal p-block elements is a promising strategy for lattice engineering of nFe 0 to tune their geometric−electronic structures and effects.…”
Section: Design Principles Of Lattice-doped Nfementioning
confidence: 99%
“…This allows the reconfiguration of the local charge density of Fe atoms (e.g., electrons are delocalized from the Fe atoms) . The altered electronic structure can induce changes in material properties, e.g., improved electrical conductivity, lowered reaction energy barriers, or increased binding energy for side reactions. These changes can enhance their reactivity and inhibit the occurrence of side reactions.…”
Section: Design Principles Of Lattice-doped Nfe0mentioning
confidence: 99%
“…We have shown that these materials can give ∼10−130 times greater rates of TCE reduction, 26,28 and others have reported similar enhance-ments with sulfidated/nitridated ZVI prepared in other ways. [29][30][31]it is not yet known if the benefits of S−N(C)−ZVI apply to other types of halocarbons, such as chlorinated alkanes, including CF. Furthermore, we have shown that the reactivity of S−N(C)−ZVI with TCE is highly dependent on the molar ratios of S/Fe ([S/Fe]) and N/Fe ([N/Fe]) used during its synthesis, 12,26,28 and it is of fundamental, as well as practical, interest to determine how these dependencies change with properties of the contaminant.…”
Section: ■ Introductionmentioning
confidence: 99%